One-Pot Synthesis of Some New Pyrido[2,3-d]pyrimidine Derivatives Catalyzed by Sodium Lauryl Sulfate in Aqueous Media - Sheng-Hui Li; Yan-Hong Shen; Na Gao; Ji-Tai Li (E-Journal of Chemistry)
A series of pyrido[2,3-d]pyrimidine derivatives were synthesized by the three-component reaction of aromatic aldehyde, malononitrile and 6-amino-4-hydroxy-2-mercaptopyrimidine catalyzed by sodium lauryl sulfate (SDS) in aqueous media. It was interesting that further aromatization took place automatically. This method provides several advantages such as easier work-up, milder reaction conditions and environmental friendly.